2017
DOI: 10.1002/cne.24206
|View full text |Cite
|
Sign up to set email alerts
|

Differential neuronal and glial expression of nuclear factor I proteins in the cerebral cortex of adult mice

Abstract: The nuclear factor I (NFI) family of transcription factors plays an important role in the development of the cerebral cortex in humans and mice. Disruption of nuclear factor IA (NFIA), nuclear factor IB (NFIB), or nuclear factor IX (NFIX) results in abnormal development of the corpus callosum, lateral ventricles, and hippocampus. However, the expression or function of these genes has not been examined in detail in the adult brain, and the cell type-specific expression of NFIA, NFIB, and NFIX is currently unkno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 88 publications
(152 reference statements)
3
34
1
Order By: Relevance
“…We find that NFIB and NFIX expression is equally widespread across all four brain regions and can be found in approximately 86% of Aldh1l1-eGFP expressing astrocytes throughout the brain (Figure 3H). Furthermore, consistent with previous findings (Chen et al, 2017), we also observed expression of NFIB and NFIX in neurons, though not to the same extent as their astrocytic expression. Taken together, these analyses suggest the presence of conserved transcription factor programs across diverse brain regions that function to maintain expression of genes that regulate core astrocytic functions.…”
Section: Region-specific Gene Signatures Display Universal Transcriptsupporting
confidence: 93%
“…We find that NFIB and NFIX expression is equally widespread across all four brain regions and can be found in approximately 86% of Aldh1l1-eGFP expressing astrocytes throughout the brain (Figure 3H). Furthermore, consistent with previous findings (Chen et al, 2017), we also observed expression of NFIB and NFIX in neurons, though not to the same extent as their astrocytic expression. Taken together, these analyses suggest the presence of conserved transcription factor programs across diverse brain regions that function to maintain expression of genes that regulate core astrocytic functions.…”
Section: Region-specific Gene Signatures Display Universal Transcriptsupporting
confidence: 93%
“…This antibody reacted with a single ∼17 kDa band on WBs using protein extracts from COS‐7 cells expressing Iba1, and lysates from adult rat testis (Imai et al, ). Both anti‐Iba1 antibodies are widely used to study microglia morphology and phagocytosis, and no cross‐reactivity with neurons and astrocytes has been reported (Chen et al, ; Cunningham et al, ; Ibañez Rodriguez et al, ; Kanazawa, Ohsawa, Sasaki, Kohsaka, & Imai, ; Ohsawa, Imai, Kanazawa, Sasaki, & Kohsaka, ; Thion et al, ). Similar staining pattern was observed for both anti‐Iba1 antibodies, and it matched that described in previous reports.…”
Section: Methodsmentioning
confidence: 99%
“…Taken together, the findings reported so far trigger the question of what causes i‐OL arrest. OPC proliferation followed by differentiation and subsequent maturation into myelinating OL is a process mediated by the expression and activity of numerous transcription factors and epigenetic programs (Chen et al, ; Emery & Lu, ; Huang et al, ; Zhang et al, ). However, little is known about their status in the dID model.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, the findings reported so far trigger the question of what causes i-OL arrest. OPC proliferation followed by differentiation and subsequent maturation into myelinating OL is a process mediated by the expression and activity of numerous transcription factors and epigenetic programs (Chen et al, 2017;Emery & Lu, 2015;Huang et al, 2016;Zhang et al, 2014) depends not only on mRNA downregulation during differentiation but also on protein export to cytoplasm, which indicates that differentiation requires both transcriptional and posttranscriptional regulation (Wang, Sdrulla, Johnson, Yokota, & Barres, 2001). The second scenario represented the absence of transcription factors promoting i-OL differentiation, including the continuous expression of Olig2, as well as the induced expression of Nkx2.2 and Sox10 and the closely related Sox9.…”
Section: Behavioral Correlation With Didmentioning
confidence: 99%